2022
DOI: 10.3390/medicina58081076
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Tocilizumab (Humanized Monoclonal Antibody) for Therapeutic Efficacy and Clinical Safety in Patients with Coronavirus Disease (COVID-19)

Abstract: Background and objectives: COVID-19 patients exhibit a broad range of manifestations, presenting with a flu-like respiratory tract infection that can advance to a systemic and severe disease characterized by pneumonia, pulmonary edema, severe damage to the airways, and acute respiratory distress syndrome (ARDS, causing fatality in 70% of COVID-19 cases). A ‘cytokine storm’ profile is found in most severely influenced COVID-19 patients. The treatment protocol of the disease also includes tocilizumab, which is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Despite our data compilation did not categorize endothelial pathology as a separated item and our models were not build specifically focusing on endothelial or coagulation processes, our results highlight the involvement of several endothelial and coagulation mediators in the mechanisms of action of the drugs, specifically found to be modulated by dexamethasone (SELE, SELP) and tocilizumab (ACE2, AGT1R, ANGPT2, CDH5, EGFR, FN1, TGFA and VEGFA). As commented, the study by Ullah et al [ 67 ], highlights the role of tocilizumab in improving performance on an institutional treatment including dexamethasone over coagulopathy control, supporting our model results. Furthermore, the evidence regarding the use of biologics targeting IL-6R –including tocilizumab–and IL-6 downstream JAK proteins since we started this study has increased [ 40 , 41 , 86 90 ], to the point that its use is recommended in the NIH guidelines for treatment of hospitalized patients requiring oxygen or assisted ventilation or oxygenation, in combination to dexamethasone [ 91 ] The methodology employed for the modelling, considering the whole human protein network and a wide range of drug-pathology relationships for the training ( S4 Table ), allow the TPMS-based models to infer biological and functional information on not-so-well documented therapeutic areas by connecting a wider biological knowledge spectrum, as shown in previous studies [ 47 , 55 , 83 , 84 ].Therefore, while the models and conclusions could be updated over time as new information is generated, potentially improving accuracy of the results and allowing exploring unanswered questions in COVID-19 evoked ARDS, our approach has provided results that are in agreement with current molecular pathophysiological and clinical knowledge, providing protein candidates as response biomarkers and supporting the role of the approach in exploring mechanistic insights on the effects of current available therapies.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Despite our data compilation did not categorize endothelial pathology as a separated item and our models were not build specifically focusing on endothelial or coagulation processes, our results highlight the involvement of several endothelial and coagulation mediators in the mechanisms of action of the drugs, specifically found to be modulated by dexamethasone (SELE, SELP) and tocilizumab (ACE2, AGT1R, ANGPT2, CDH5, EGFR, FN1, TGFA and VEGFA). As commented, the study by Ullah et al [ 67 ], highlights the role of tocilizumab in improving performance on an institutional treatment including dexamethasone over coagulopathy control, supporting our model results. Furthermore, the evidence regarding the use of biologics targeting IL-6R –including tocilizumab–and IL-6 downstream JAK proteins since we started this study has increased [ 40 , 41 , 86 90 ], to the point that its use is recommended in the NIH guidelines for treatment of hospitalized patients requiring oxygen or assisted ventilation or oxygenation, in combination to dexamethasone [ 91 ] The methodology employed for the modelling, considering the whole human protein network and a wide range of drug-pathology relationships for the training ( S4 Table ), allow the TPMS-based models to infer biological and functional information on not-so-well documented therapeutic areas by connecting a wider biological knowledge spectrum, as shown in previous studies [ 47 , 55 , 83 , 84 ].Therefore, while the models and conclusions could be updated over time as new information is generated, potentially improving accuracy of the results and allowing exploring unanswered questions in COVID-19 evoked ARDS, our approach has provided results that are in agreement with current molecular pathophysiological and clinical knowledge, providing protein candidates as response biomarkers and supporting the role of the approach in exploring mechanistic insights on the effects of current available therapies.…”
Section: Discussionsupporting
confidence: 88%
“…A recent study in critically ill patients treated with dexamethasone show that inflammatory markers, such as the C-reactive protein (CRP), lactate dehydrogenase, ferritin and the neutrophil-lymphocyte ratio were reduced upon tocilizumab treatment (in patients treated with a treatment combination including corticosteroids) [ 66 ]. In another study comparing the change from baseline between adding tocilizumab or not, although they found a greater reduction in CRP and ferritin levels when adding tocilizumab, the reduction was not significantly different than the reduction induced by the treatment without tocilizumab [ 67 ]; they did find, however, a significant difference when evaluating coagulation parameters, such as activated partial thromboplastin time, prothrombin time and platelet levels. Interestingly, Ponthieux et al [ 68 ], although noting reduced CRP levels, found an increase in IL-1β, -2, -4, -10, -12p70, -18, and sIL-6R days 2–4 after tocilizumab alone treatment in a small cohort of 15 critically ill patients, supporting the relevance of the combination with corticosteroids for an additive anti-inflammatory effect.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in numerous countries, several factors have limited the use of tocilizumab, such as drug shortages, high cost or late approval (December 2021 in Europe, December 2022 in the USA). Therefore, real-life data on tocilizumab treatment remain scarce, especially in patients infected with delta or omicron VOCs [13][14][15]. Moreover, its use is questionable in omicron cases.…”
Section: Introductionmentioning
confidence: 99%
“…Sami Ullah et al, conducted an open-label, randomized clinical trial to investigate the impact of TCZ in patients with COVID-19 while focusing on the remission of the cytokine release syndrome. The study did not reveal any statistically significant difference between the TCZ and control group in inflammatory markers (CRP, ferritin, D-dimer or LDH) while the coagulation parameters showed a significant difference in the median change from baseline between the TCZ and control group (INR 0.12 vs. − 0.07; p ≤ 0.001; aPTT 0.42 vs. − 1.16; p ≤ 0.001; prothrombin time (PT) 0.31 vs. − 0.96; p ≤ 0.001; and platelet count − 12.34 vs. − 1.47; p = 0.012) 24 . In the Atallah et al 20 case series, they observed a decline in inflammatory markers, such as D-dimer and fibrinogen, in hospitalized patients with COVID-19 while being on TCZ therapy.…”
Section: Discussionmentioning
confidence: 98%